(untitled) (Biological Sciences - PJSIR, 1995)
Three varieties (suncross-843, NK-265, NK-212) of sunflower seeds wereanalysed for their proximate compo- sition. Cultivar NK-212 was selected for further treatments, in view or its desirable nutritive and other physico- chemical characteristics. Application of different methods/treatments resulted in reduction of fibre from 24.41 to 18.34% and chlorogenic acid from 3.34 to 1.02%. Biological evaluation studies on the processed meal indicated considerable improvements in the nutritional qualities.